2019
DOI: 10.1016/j.devcel.2018.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional Heterogeneity of Beta Cells in the Intact Pancreas

Abstract: Highlights d Islets contain a minority of ''extreme'' beta cells with elevated insulin mRNA levels d Elevated proinsulin yet lower insulin protein suggests these are basal secretors d Extreme cells exhibit discordant apical-basal mRNA and protein localization d The proportion of extreme cells increases in insulin-resistant animals

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
78
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(85 citation statements)
references
References 87 publications
7
78
0
Order By: Relevance
“…Isolated islets and single human β-cells from people with type 2 diabetes have reduced INS expression on average (Segerstolpe et al, 2016;Yang et al, 2011). Extreme β-cell were significantly more common in diabetic db/db mice (Farack et al, 2019). We found that the Ins2(GFP) HIGH state was associated with significant vulnerability to cellular stress, so having an excess number of Ins2(GFP) HIGH β-cells at a given time may negatively affect islet health and robustness.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Isolated islets and single human β-cells from people with type 2 diabetes have reduced INS expression on average (Segerstolpe et al, 2016;Yang et al, 2011). Extreme β-cell were significantly more common in diabetic db/db mice (Farack et al, 2019). We found that the Ins2(GFP) HIGH state was associated with significant vulnerability to cellular stress, so having an excess number of Ins2(GFP) HIGH β-cells at a given time may negatively affect islet health and robustness.…”
Section: Discussionmentioning
confidence: 78%
“…Indeed, functional β-cell heterogeneity is well established (Benninger and Hodson, 2018), including cellular specialization for islet cell synchronization, insulin secretion, insulin production, and marker gene expression (Bader et al, 2016;Dorrell et al, 2016;Heimberg et al, 1993;Johnston et al, 2016;Kiekens et al, 1992;Kolic and Johnson, 2016;Ling et al, 1998;Pipeleers, 1992;van der Meulen et al, 2017;Wills et al, 2016;Xin et al, 2018). For example, recent in situ imaging has revealed the existence of extreme β-cells, defined as having >2 fold Ins2 mRNA than the median expression as measured by single-molecule fluorescence in situ hybridization (Benninger and Hodson, 2018;Farack et al, 2019). Single cell RNA sequencing has shown that human β-cells also express INS over a similarly wide range (Xin et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…We thus hypothesize that acinar-I cells represent a different stage of acinar cell activation that could be converted to acinar-S cells following hormonal or nutritional stimulation, resembling the different activation states recently identified in human and mouse β cells 38,39 . Moreover, acinar-I cells might constitute a source of cell replacement for acinar-S cells, which are subject to high level of ER stress and therefore more prone to cell death via apoptosis.…”
mentioning
confidence: 62%
“…In addition, a recent study identified a population of β cells termed "extreme" β cells located in the center of the islet. These cells were characterized by a distinct polarization pattern and higher proinsulin and ribosomal RNA content (76). Additional subpopulations of β cells, including "hub" β cells that demonstrate pacemaker activities to coordinate insulin response to glucose and "virgin" β cells, which are postulated to represent a population of immature β cells that form a neogenic niche at the periphery of the islet, have also been identified (77,78); however, the extent to which these populations represent distinct β cell subtypes versus a phenotypic continuum of a homogeneous cell population remains to be seen.…”
Section: β Cell Dedifferentiationmentioning
confidence: 99%